Representation, recognition and respect in world politics the case of Iran-US relations - Duncombe, Constance (Manchester University Press, 2019)
In 2015, Iran and the US reached an agreement on the framework for a long-term deal that allows Iran limited nuclear technological capacity in exchange for the lifting of debilitating economic sanctions. However, questions remain about how best to explain the success of this deal considering the decades of animosity between Iran and the US, which previously attempts on both sides to reach an amicable agreement. It also confronts increasing concerns about the future of the agreement under the Trump administrations.